Agricultural carbon emission efficiency evaluation and influencing factors in Zhejiang province, China - Li, Jingjie; Li, Shanwei; Liu, Qian; Ding, Junli (Frontiers in Environmental Science, 2022)
To clarify the agricultural carbon emission efficiency and influencing factors in Zhejiang Province, China, and provide reference basis and policy inspiration for the practical promotion of agricultural low-carbon production. Based on the classic IPCC carbon emission calculation theory, this paper calculates the agricultural carbon emissions and carbon emission intensity in Zhejiang Province from 2011 to 2020 based on the input of agricultural materials, land irrigation, and farmland tillage. The LMDI model is adapted to carry out the influence factors analysis using the grey prediction model GM(1, 1) prediction in 2020-2040 carbon emissions. The results showed that the agricultural carbon emissions and carbon emission intensity in Zhejiang Province showed a downward trend. Further combined with the static efficiency analysis, it is concluded that Shaoxing, Hangzhou, Jiaxing, and Huzhou are the cities with low emission and high efficiency, and Wenzhou is the city with high emission and low efficiency. Dynamic efficiency analysis shows that the improvement of Total factor productivity(TFP) results from the joint action of Technical Progress Efficiency (TECH) and Technical Efficiency (EFF). Tech is greater than Eff, and Scale Efficiency (SE) and Pure Technical Efficiency (PTE) contributions change with the years. In general, the contribution of PTE is more significant than that of SE, and its improvement mainly rests on technical progress. Further decomposition of technical efficiency shows that the role of pure technical efficiency is more evident than that of scale efficiency. Among the factors influencing agricultural carbon emission efficiency, agricultural carbon emission intensity and labor force size have inhibiting effects on agricultural carbon emission efficiency growth. In contrast, agricultural, industrial structure, economic development, and urbanization positively affect agricultural carbon emission efficiency. The prediction results show that only Zhoushan City, Zhejiang Province, will not reach the peak of agricultural carbon emissions by 2030.